Potensi Beberapa Kultivar Puring (Codiaeum variegatum L.) sebagai Fitoremediasi pada Tanah Tercemar Logam Berat Pb (Timbal) - Regita Hilda Meidina; Anis Rosyidah; Indiyah Murwani (AGRONISMA, 2019)
Land contaminated with heavy metals and toxic substances is an environmental problem that must be addressed immediately. Heavy metals in the soil affect plant growth, productivity and ultimately lead to human health.The amount of heavy metals present in plants is influenced by their concentration in the soil, the physical-chemical conditions of the soil, the species and plant genotypes involved. The study aimed to obtain Croton (Codiaeum variegatum L.) cultivars that were tolerant of lead (Pb) heavy metal stress, studying the phytoremediation strategy of croton cultivars (Codiaeum variegatum L.) in absorbing heavy metal lead (Pb) from the soil. The study was conducted at the Greenhouse of the Faculty of Agriculture, Islamic University of Malang, from August to November 2018. The results showed that the growth in number of leaves and plant height showed no significant effect, while the total root length and leaf area of each cultivar were significant. Cultivar that hastolerance of lead (Pb) heavy metal stress is Jago cultivar, indicated by high Pb concentrations found at the roots of 0.48060 ppm, and also has the largest total root length of 5748.817 cm. The calculation results obtained TF values <1 and BCF> 1, so the phytoremediation strategies of croton cultivars exposed by Pb from the soil include to phytostabilization.